Lower Bounds on Portfolio Performance: An Extension of the Immunization Strategy - Marshall, William J.; Yawitz, Jess B. (Journal of Financial and Quantitative Analysis, 1982)
William J. Marshall, Jess B. Yawitz, Lower Bounds on Portfolio Performance: An Extension of the Immunization Strategy, The Journal of Financial and Quantitative Analysis, Vol. 17, No. 1 (Mar., 1982), pp. 101-113